Colored sand self-leveling floor coating and preparation method thereof
By preparing color sand self-leveling floor coatings, curing accelerators and reinforcement fillers are prepared by reactions such as cashew phenol. Combined with epoxy resin and color sand and other raw materials, the problem of color sand self-leveling floor coatings being worn after long-term use and water soaked after water, achieving wear, water resistance and high toughness of the coating.
Patent Information
- Application Number
- CN202411629379.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-15
AI Technical Summary
At this stage, colored sand self-leveling floor coatings are prone to obvious wear after long-term use, and may appear on the bridge side after being soaked in water, affecting normal use.
By preparing a colored sand self-leveling floor coating, the intermediate is prepared by reacting raw materials such as cashew phenol, potassium carbonate, allyl chloride, etc., and polymerizing it with tetramethylcyclotetrasiloxane, octamethylcyclotetrasiloxane, etc. to obtain curing accelerator and reinforcement filler, combined with raw materials such as epoxy resin, colored sand, and talc powder, and the coating is prepared by blending reaction.
It improves the wear resistance and water resistance of the paint, delays crack propagation, enhances the fracture toughness and impact resistance of the paint, and significantly improves the service life and performance of colored sand self-leveling floors.
Smart Images

Figure BDA0005135522450000121
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of colored sand self-leveling preparation, and in particular to a colored sand self-leveling floor coating and a preparation method thereof. Background Art
[0002] Epoxy resin is widely used in the decoration of building floors, thanks to the rapid development of solvent-free liquid epoxy resin, as well as the improvement of construction technology and equipment. So far, epoxy resin floor products are complete, including solvent-based epoxy wear-resistant floor coatings, water-based epoxy floor coatings, outdoor weather-resistant floor coatings, epoxy self-leveling floor coatings and anti-static epoxy floor coatings. Epoxy colored sand self-leveling is a new type of seamless integrated composite decorative floor composed of colored quartz sand and special epoxy resin. Through the free combination of one or more different colored quartz sands, a colorful decorative pattern is formed. The colored sand used in epoxy colored sand self-leveling is generally natural colored sand. Natural colored sand uses natural colored marble, granite and other sand particles. The color is natural, never changes color, has good compressive resistance, and the construction is close to the effect of natural stone. However, since epoxy resin is brittle after curing, the self-leveling is prone to damage or wear during use. At the same time, bridge edges will appear after being soaked in water, affecting normal use. Summary of the invention
[0003] The purpose of the present invention is to provide a colored sand self-leveling floor coating and a preparation method thereof, so as to solve the problem that the colored sand self-leveling floor coating at the current stage will be obviously worn out after long-term use, and will have bridging edges after being soaked in water.
[0004] The purpose of the present invention can be achieved through the following technical solutions:
[0005] A method for preparing a colored sand self-leveling floor coating comprises the following steps:
[0006] Step A1: Cardanol, potassium carbonate, allyl chloride and toluene are mixed evenly, and reacted at a speed of 150-200 r / min and a temperature of 20-25° C. for 3-5 hours to obtain intermediate 1; intermediate 1, tetramethylcyclotetrasiloxane, chloroplatinic acid and DMF are mixed evenly, nitrogen is introduced for protection, and reacted at a speed of 120-150 r / min and a temperature of 70-80° C. for 3-5 hours to obtain intermediate 2;
[0007] Step A2: The intermediate 2, octamethylcyclotetrasiloxane, tetramethylammonium hydroxide, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and dimethyl sulfoxide are uniformly mixed, nitrogen is introduced for protection, and the reaction is carried out for 3-5 hours at a speed of 120-150 r / min and a temperature of 105-110° C. to obtain a curing accelerator, and the modified filler is dispersed in ethanol, and KH560 and deionized water are added under stirring at a speed of 200-300 r / min and a temperature of 25-30° C., and the reaction is carried out for 2-3 hours to obtain a reinforced filler;
[0008] Step A3: Weigh the following raw materials in parts by weight: 80-90 parts of epoxy resin E-51, 10-20 parts of reinforcing filler and 10-20 parts of 501A epoxy reactive diluent, mix them evenly to obtain component A, weigh the following raw materials in parts by weight: 15-20 parts of curing agent, 5-10 parts of curing accelerator, 100-150 parts of colored sand, 2-5 parts of talcum powder, 0.3-1 parts of dispersant, 0.3-0.5 parts of defoaming agent and 5-10 parts of leveling agent, mix them evenly to obtain component B, mix component A and component B to obtain colored sand self-leveling floor coating.
[0009] Furthermore, the molar ratio of cardanol, potassium carbonate and allyl chloride in step A1 is 1:1.1:1, the molar ratio of intermediate 1 and tetramethylcyclotetrasiloxane is 1:4, and the amount of chloroplatinic acid used is 1‰ of the mass of tetramethylcyclotetrasiloxane.
[0010] Furthermore, the molar ratio of the intermediate 2, octamethylcyclotetrasiloxane, tetramethylammonium hydroxide and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane described in step A2 is 1.2:1.2:3:2, and the amount of KH560 used is 5% of the mass of the modified filler.
[0011] Further, the modified filler is prepared by the following steps:
[0012] Step B1: Disperse cellulose in N,N-dimethylacetamide, introduce nitrogen protection, stir and add anhydrous lithium chloride at a speed of 120-150r / min and a temperature of 100-110°C, stir for 3-5h, cool to 8-10°C, add triethylamine and p-toluenesulfonyl chloride, react for 20-25h to obtain pretreated cellulose, disperse the pretreated cellulose in N,N-dimethylacetamide, stir and add ammonia water at a speed of 60-80r / min and a temperature of 140-145°C, react for 20-25h to obtain amino cellulose;
[0013] Step B2: The amino cellulose, maleic anhydride, triethylamine and N, N-dimethylformamide are mixed uniformly, and reacted for 6-8 hours at a speed of 120-150 r / min and a temperature of 80-90° C. to obtain modified cellulose; tetramethyl tri-3-trifluoropropyl cyclotetrasiloxane, octamethyl cyclotetrasiloxane, tetramethyl ammonium hydroxide, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and dimethyl sulfoxide are mixed uniformly, nitrogen is introduced for protection, and the reaction is carried out for 3-5 hours at a speed of 120-150 r / min and a temperature of 105-110° C. to obtain a modifier;
[0014] Step B3: The modifier, allyl glycidyl ether and N, N-dimethylformamide are mixed evenly, and reacted for 6-8 hours at a speed of 150-200 r / min, a temperature of 60-70°C, and a pH value of 9-10 to obtain a modified monomer. The modified monomer, modified cellulose, 1-hexene, azobisisobutyronitrile and N, N-dimethylformamide are mixed evenly, nitrogen is introduced for protection, and the speed is 120-150 r / min, The temperature is 70-75°C, and the reaction is carried out for 10-12 hours to obtain a modified filler.
[0015] Furthermore, the mass ratio of cellulose, anhydrous lithium chloride, triethylamine and p-toluenesulfonyl chloride in step B1 is 10 mg: 1 mg: 1 g: 5 g, the amount ratio of pretreated cellulose, N, N-dimethylacetamide and ammonia water is 1 mL: 10 mL: 20 mL, and the mass fraction of ammonia water is 30%.
[0016] Furthermore, the molar ratio of the amino group on the aminated cellulose in step B2, maleic anhydride and triethylamine is 1:1:1.2, and the molar ratio of tetramethyltri-3-trifluoropropylcyclotetrasiloxane, octamethylcyclotetrasiloxane, tetramethylammonium hydroxide and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane is 1.5:0.9:3:2.
[0017] Furthermore, the molar ratio of the modifier described in step B3 to allyl glycidyl ether is 1:4, the usage ratio of the modified monomer, modified cellulose and 1-hexene is 60 mmol: 1 g: 40 mmol, and the usage of azobisisobutyronitrile is 1% of the mass of 1-hexene.
[0018] The beneficial effects of the present invention are as follows: a colored sand self-leveling floor coating prepared by the present invention comprises component A and component B, wherein component A comprises the following raw materials: epoxy resin E-51, reinforcing filler and 501A epoxy active diluent, and component B comprises the following raw materials: curing agent, curing accelerator, colored sand, talcum powder, dispersant, defoaming agent and leveling agent, wherein the curing accelerator uses cardanol and allyl chloride as raw materials, and the hydroxyl group on the cardanol reacts with the chlorine atom site on the allyl chloride under the action of potassium carbonate to obtain intermediate 1, and intermediate 1 is reacted with tetramethylcyclotetrasiloxane so that the double bond on intermediate 1 reacts with the SiH bond on tetramethylcyclotetrasiloxane to obtain intermediate 2, and intermediate 2 and octamethylcyclotetrasiloxane are ring-opened, and then polymerized with 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane to obtain a curing accelerator.
[0019] The reinforcing filler is prepared by treating cellulose as a raw material with p-toluenesulfonyl chloride so that the hydroxyl group on the cellulose reacts with the acyl chloride on the p-toluenesulfonyl chloride to obtain pretreated cellulose, treating the pretreated cellulose with ammonia water so that the p-toluenesulfonic acid ester on the pretreated cellulose is ammoniolyzed to obtain aminated cellulose, reacting the aminated cellulose with maleic anhydride so that the amino group on the aminated cellulose reacts with the maleic anhydride to form a maleimide structure, opening the tetramethyl tri-3-trifluoropropyl cyclotetrasiloxane and octamethyl cyclotetrasiloxane, and then reacting with 1,3-bis(3-aminopropyl)-1-(2-nitropropoxy)-1-yl)-cyclohexane. )-1,1,3,3-tetramethyldisiloxane is polymerized to obtain a modifier, the modifier is reacted with allyl glycidyl ether so that the amino group on the modifier reacts with the epoxy group on the allyl glycidyl ether to obtain a modified monomer, the modified monomer, modified cellulose and 1-hexene are copolymerized under the action of azobisisobutyronitrile, the surface of the modified cellulose is coated with a copolymer containing a silicone chain segment to obtain a modified filler, the modified filler is treated with KH560 so that the silicon-oxygen bonds on the KH560 are hydrolyzed and grafted with the hydroxyl groups on the modified filler to obtain a reinforced filler.
[0020] After component A and component B are blended, since the modified filler contains epoxy groups on the surface and the curing accelerator contains amino groups, both of them can participate in the curing of epoxy resin molecules. The addition of reinforcing fillers can increase the molecular cross-linking density, thereby improving the wear resistance of the material. At the same time, cellulose is used as the base material of the reinforcing filler, which can increase the crack propagation resistance of the coating, delay the propagation of cracks, and form fiber bridges at the crack tips, thereby improving the fracture toughness of the coating. At the same time, the surface is coated with a copolymer containing silicone chain segments, which can increase the hydrophobic effect of the modified filler and cooperate with the long-chain alkyl on the curing accelerator to increase the water resistance of the coating. The long-chain alkyl can form a transition layer at the interface between the epoxy resin molecules. This transition layer can increase the crack propagation resistance inside the material, thereby improving the toughness of the coating. DETAILED DESCRIPTION
[0021] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0022] Embodiment 1, a method for preparing a colored sand self-leveling floor coating, specifically comprising the following steps:
[0023] Step A1: Cardanol, potassium carbonate, allyl chloride and toluene are mixed evenly, and reacted at a speed of 150 r / min and a temperature of 20° C. for 3 h to obtain intermediate 1; intermediate 1, tetramethylcyclotetrasiloxane, chloroplatinic acid and DMF are mixed evenly, nitrogen is introduced for protection, and reacted at a speed of 120 r / min and a temperature of 70° C. for 3 h to obtain intermediate 2;
[0024] Step A2: The intermediate 2, octamethylcyclotetrasiloxane, tetramethylammonium hydroxide, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and dimethyl sulfoxide are uniformly mixed, nitrogen is introduced for protection, and the reaction is carried out for 3 hours at a speed of 120 r / min and a temperature of 105° C. to obtain a curing accelerator, and the modified filler is dispersed in ethanol, and KH560 and deionized water are added under stirring at a speed of 200 r / min and a temperature of 25° C., and the reaction is carried out for 2 hours to obtain a reinforced filler;
[0025] Step A3: Weigh the following raw materials in parts by weight: 80 parts of epoxy resin E-51, 10 parts of reinforcing filler and 10 parts of 501A epoxy reactive diluent, mix them evenly to obtain component A, weigh the following raw materials in parts by weight: 15 parts of curing agent, 5 parts of curing accelerator, 100 parts of colored sand, 2 parts of talcum powder, 0.3 parts of dispersant, 0.3 parts of defoaming agent and 5 parts of leveling agent, mix them evenly to obtain component B, mix component A and component B to obtain colored sand self-leveling floor coating.
[0026] The molar ratio of cardanol, potassium carbonate and allyl chloride in step A1 is 1:1.1:1, the molar ratio of intermediate 1 and tetramethylcyclotetrasiloxane is 1:4, and the amount of chloroplatinic acid used is 1‰ of the mass of tetramethylcyclotetrasiloxane.
[0027] The molar ratio of intermediate 2, octamethylcyclotetrasiloxane, tetramethylammonium hydroxide and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane described in step A2 is 1.2:1.2:3:2, and the amount of KH560 used is 5% of the mass of the modified filler.
[0028] The curing agent described in step A3 is ethylenediamine, the dispersant is BYK-142, the defoaming agent is BYK-066N, and the leveling agent is BYK-302.
[0029] The modified filler is prepared by the following steps:
[0030] Step B1: Disperse cellulose in N,N-dimethylacetamide, introduce nitrogen protection, stir and add anhydrous lithium chloride at a speed of 120 r / min and a temperature of 100°C, stir for 3 hours, cool to 8°C, add triethylamine and p-toluenesulfonyl chloride, react for 20 hours to obtain pretreated cellulose, disperse the pretreated cellulose in N,N-dimethylacetamide, stir and add ammonia water at a speed of 60 r / min and a temperature of 140°C, react for 20 hours to obtain amino cellulose;
[0031] Step B2: The amino cellulose, maleic anhydride, triethylamine and N, N-dimethylformamide are mixed uniformly, and reacted at a speed of 120 r / min and a temperature of 80°C for 6 hours to obtain modified cellulose; tetramethyl tri-3-trifluoropropyl cyclotetrasiloxane, octamethyl cyclotetrasiloxane, tetramethyl ammonium hydroxide, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and dimethyl sulfoxide are mixed uniformly, nitrogen is introduced for protection, and the reaction is carried out at a speed of 120 r / min and a temperature of 105°C for 3 hours to obtain a modifier;
[0032] Step B3: The modifier, allyl glycidyl ether and N,N-dimethylformamide are mixed evenly, and reacted for 6 hours at a speed of 150 r / min, a temperature of 60°C and a pH value of 9 to obtain a modified monomer. The modified monomer, modified cellulose, 1-hexene, azobisisobutyronitrile and N,N-dimethylformamide are mixed evenly, nitrogen is introduced for protection, and reacted for 10 hours at a speed of 120 r / min and a temperature of 70°C to obtain a modified filler.
[0033] The mass ratio of cellulose, anhydrous lithium chloride, triethylamine and p-toluenesulfonyl chloride in step B1 is 10 mg: 1 mg: 1 g: 5 g, the amount ratio of pretreated cellulose, N, N-dimethylacetamide and ammonia water is 1 mL: 10 mL: 20 mL, and the mass fraction of ammonia water is 30%.
[0034] The molar ratio of the amino group on the aminated cellulose in step B2, maleic anhydride and triethylamine is 1:1:1.2, and the molar ratio of tetramethyltri-3-trifluoropropylcyclotetrasiloxane, octamethylcyclotetrasiloxane, tetramethylammonium hydroxide and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane is 1.5:0.9:3:2.
[0035] The molar ratio of the modifier and allyl glycidyl ether described in step B3 is 1:4, the amount ratio of the modified monomer, modified cellulose and 1-hexene is 60mmo l:1g:40mmo l, and the amount of azobisisobutyronitrile is 1% of the mass of 1-hexene.
[0036] Embodiment 2: A method for preparing a colored sand self-leveling floor coating, comprising the following steps:
[0037] Step A1: Cardanol, potassium carbonate, allyl chloride and toluene are mixed evenly, and the mixture is reacted at a speed of 150 r / min and a temperature of 25° C. for 4 h to obtain intermediate 1; intermediate 1, tetramethylcyclotetrasiloxane, chloroplatinic acid and DMF are mixed evenly, nitrogen is introduced for protection, and the mixture is reacted at a speed of 120 r / min and a temperature of 75° C. for 4 h to obtain intermediate 2;
[0038] Step A2: The intermediate 2, octamethylcyclotetrasiloxane, tetramethylammonium hydroxide, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and dimethyl sulfoxide are uniformly mixed, nitrogen is introduced for protection, and the reaction is carried out for 4 hours at a speed of 120 r / min and a temperature of 110° C. to obtain a curing accelerator, and the modified filler is dispersed in ethanol, and KH560 and deionized water are added under stirring at a speed of 200 r / min and a temperature of 30° C., and the reaction is carried out for 2 hours to obtain a reinforced filler;
[0039] Step A3: Weigh the following raw materials in parts by weight: 85 parts of epoxy resin E-51, 15 parts of reinforcing filler and 15 parts of 501A epoxy reactive diluent, mix them evenly to obtain component A, weigh the following raw materials in parts by weight: 18 parts of curing agent, 8 parts of curing accelerator, 125 parts of colored sand, 3.5 parts of talcum powder, 0.6 parts of dispersant, 0.4 parts of defoaming agent and 8 parts of leveling agent, mix them evenly to obtain component B, mix component A and component B to obtain colored sand self-leveling floor coating.
[0040] The molar ratio of cardanol, potassium carbonate and allyl chloride in step A1 is 1:1.1:1, the molar ratio of intermediate 1 and tetramethylcyclotetrasiloxane is 1:4, and the amount of chloroplatinic acid used is 1‰ of the mass of tetramethylcyclotetrasiloxane.
[0041] The molar ratio of intermediate 2, octamethylcyclotetrasiloxane, tetramethylammonium hydroxide and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane described in step A2 is 1.2:1.2:3:2, and the amount of KH560 used is 5% of the mass of the modified filler.
[0042] The curing agent described in step A3 is hexamethylenediamine, the dispersant is BYK-163, the defoaming agent is BYK-011, and the leveling agent is BYK-320.
[0043] The modified filler is prepared by the following steps:
[0044] Step B1: Disperse cellulose in N,N-dimethylacetamide, introduce nitrogen protection, stir and add anhydrous lithium chloride at a speed of 120 r / min and a temperature of 105°C, stir for 4 hours, cool to 9°C, add triethylamine and p-toluenesulfonyl chloride, react for 25 hours to obtain pretreated cellulose, disperse the pretreated cellulose in N,N-dimethylacetamide, stir and add ammonia water at a speed of 60 r / min and a temperature of 145°C, react for 20 hours to obtain amino cellulose;
[0045] Step B2: The amino cellulose, maleic anhydride, triethylamine and N, N-dimethylformamide are mixed uniformly, and reacted at a speed of 120 r / min and a temperature of 85°C for 7 hours to obtain modified cellulose; tetramethyl tri-3-trifluoropropyl cyclotetrasiloxane, octamethyl cyclotetrasiloxane, tetramethyl ammonium hydroxide, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and dimethyl sulfoxide are mixed uniformly, nitrogen is introduced for protection, and the reaction is carried out at a speed of 120 r / min and a temperature of 110°C for 4 hours to obtain a modifier;
[0046] Step B3: The modifier, allyl glycidyl ether and N,N-dimethylformamide are mixed evenly, and reacted for 7 hours at a speed of 150 r / min, a temperature of 65°C and a pH value of 9 to obtain a modified monomer. The modified monomer, modified cellulose, 1-hexene, azobisisobutyronitrile and N,N-dimethylformamide are mixed evenly, nitrogen is introduced for protection, and reacted for 10 hours at a speed of 120 r / min and a temperature of 75°C to obtain a modified filler.
[0047] The mass ratio of cellulose, anhydrous lithium chloride, triethylamine and p-toluenesulfonyl chloride in step B1 is 10 mg: 1 mg: 1 g: 5 g, the amount ratio of pretreated cellulose, N, N-dimethylacetamide and ammonia water is 1 mL: 10 mL: 20 mL, and the mass fraction of ammonia water is 30%.
[0048] The molar ratio of the amino group on the aminated cellulose in step B2, maleic anhydride and triethylamine is 1:1:1.2, and the molar ratio of tetramethyltri-3-trifluoropropylcyclotetrasiloxane, octamethylcyclotetrasiloxane, tetramethylammonium hydroxide and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane is 1.5:0.9:3:2.
[0049] The molar ratio of the modifier and allyl glycidyl ether described in step B3 is 1:4, the amount ratio of the modified monomer, modified cellulose and 1-hexene is 60mmo l:1g:40mmo l, and the amount of azobisisobutyronitrile is 1% of the mass of 1-hexene.
[0050] Embodiment 3, a method for preparing a colored sand self-leveling floor coating, specifically comprising the following steps:
[0051] Step A1: Cardanol, potassium carbonate, allyl chloride and toluene are mixed evenly, and reacted at a speed of 200 r / min and a temperature of 25° C. for 5 h to obtain intermediate 1; intermediate 1, tetramethylcyclotetrasiloxane, chloroplatinic acid and DMF are mixed evenly, nitrogen is introduced for protection, and the reaction is carried out at a speed of 150 r / min and a temperature of 80° C. for 5 h to obtain intermediate 2;
[0052] Step A2: The intermediate 2, octamethylcyclotetrasiloxane, tetramethylammonium hydroxide, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and dimethyl sulfoxide are uniformly mixed, nitrogen is introduced for protection, and the reaction is carried out for 5 hours at a speed of 150 r / min and a temperature of 110° C. to obtain a curing accelerator, and the modified filler is dispersed in ethanol, and KH560 and deionized water are added under stirring at a speed of 300 r / min and a temperature of 30° C., and the reaction is carried out for 3 hours to obtain a reinforced filler;
[0053] Step A3: Weigh the following raw materials in parts by weight: 90 parts of epoxy resin E-51, 20 parts of reinforcing filler and 20 parts of 501A epoxy reactive diluent, mix them evenly to obtain component A, weigh the following raw materials in parts by weight: 20 parts of curing agent, 10 parts of curing accelerator, 150 parts of colored sand, 5 parts of talcum powder, 1 part of dispersant, 0.5 parts of defoaming agent and 10 parts of leveling agent, mix them evenly to obtain component B, mix component A and component B to obtain colored sand self-leveling floor coating.
[0054] The molar ratio of cardanol, potassium carbonate and allyl chloride in step A1 is 1:1.1:1, the molar ratio of intermediate 1 and tetramethylcyclotetrasiloxane is 1:4, and the amount of chloroplatinic acid used is 1‰ of the mass of tetramethylcyclotetrasiloxane.
[0055] The molar ratio of intermediate 2, octamethylcyclotetrasiloxane, tetramethylammonium hydroxide and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane described in step A2 is 1.2:1.2:3:2, and the amount of KH560 used is 5% of the mass of the modified filler.
[0056] The curing agent described in step A3 is diethylenetriamine, the dispersant is BYK-190, the defoaming agent is BYK-028, and the leveling agent is BYK-420.
[0057] The modified filler is prepared by the following steps:
[0058] Step B1: Disperse cellulose in N,N-dimethylacetamide, introduce nitrogen protection, stir and add anhydrous lithium chloride at a speed of 150 r / min and a temperature of 110°C, stir for 5 hours, cool to 10°C, add triethylamine and p-toluenesulfonyl chloride, react for 25 hours to obtain pretreated cellulose, disperse the pretreated cellulose in N,N-dimethylacetamide, stir and add ammonia water at a speed of 80 r / min and a temperature of 145°C, react for 25 hours to obtain amino cellulose;
[0059] Step B2: The amino cellulose, maleic anhydride, triethylamine and N, N-dimethylformamide are mixed uniformly, and reacted at a speed of 150 r / min and a temperature of 90° C. for 8 hours to obtain modified cellulose; tetramethyl tri-3-trifluoropropyl cyclotetrasiloxane, octamethyl cyclotetrasiloxane, tetramethyl ammonium hydroxide, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and dimethyl sulfoxide are mixed uniformly, nitrogen is introduced for protection, and the reaction is carried out at a speed of 150 r / min and a temperature of 110° C. for 5 hours to obtain a modifier;
[0060] Step B3: The modifier, allyl glycidyl ether and N,N-dimethylformamide are mixed evenly, and reacted for 8 hours at a speed of 200 r / min, a temperature of 70°C and a pH value of 10 to obtain a modified monomer. The modified monomer, modified cellulose, 1-hexene, azobisisobutyronitrile and N,N-dimethylformamide are mixed evenly, nitrogen is introduced for protection, and reacted for 12 hours at a speed of 150 r / min and a temperature of 75°C to obtain a modified filler.
[0061] The mass ratio of cellulose, anhydrous lithium chloride, triethylamine and p-toluenesulfonyl chloride in step B1 is 10 mg: 1 mg: 1 g: 5 g, the amount ratio of pretreated cellulose, N, N-dimethylacetamide and ammonia water is 1 mL: 10 mL: 20 mL, and the mass fraction of ammonia water is 30%.
[0062] The molar ratio of the amino group on the aminated cellulose in step B2, maleic anhydride and triethylamine is 1:1:1.2, and the molar ratio of tetramethyltri-3-trifluoropropylcyclotetrasiloxane, octamethylcyclotetrasiloxane, tetramethylammonium hydroxide and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane is 1.5:0.9:3:2.
[0063] The molar ratio of the modifier and allyl glycidyl ether described in step B3 is 1:4, the amount ratio of the modified monomer, modified cellulose and 1-hexene is 60mmo l:1g:40mmo l, and the amount of azobisisobutyronitrile is 1% of the mass of 1-hexene.
[0064] Comparative Example 1: Compared with Example 1, no curing accelerator was added to this comparative example, and the remaining steps were the same.
[0065] Comparative Example 2: Compared with Example 1, this comparative example uses a modified filler instead of a reinforcing filler, and the remaining steps are the same.
[0066] Comparative Example 3: Compared with Example 1, this comparative example uses cellulose instead of the modified filler, and the other steps are the same.
[0067] The colored sand self-leveling floor coatings prepared in Examples 1-3 and Comparative Examples 1-3 were made into test panels according to the standard of GB / T22374-2018 and left for 7 days. The dry film thickness was 1 mm. The pencil hardness, abrasion resistance and water resistance were tested. A 1000 g steel ball with a height of 100 mm was used to test the impact resistance. The test results are shown in Table 1 below.
[0068] Table 1
[0069]
[0070] It can be seen from the above table that the present invention has good wear-resistant and water-resistant effects.
[0071] The above contents are merely examples and explanations of the concept of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A method for preparing a colored sand self-leveling floor coating, characterized in that: The specific steps include: Step A1: Cardanol, potassium carbonate, allyl chloride and toluene are mixed for reaction to obtain intermediate 1, intermediate 1, tetramethylcyclotetrasiloxane, chloroplatinic acid and DMF are uniformly mixed, nitrogen protection is introduced, and the reaction is carried out to obtain intermediate 2; Step A2: The intermediate 2, octamethylcyclotetrasiloxane, tetramethylammonium hydroxide, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and dimethyl sulfoxide are uniformly mixed, nitrogen is introduced for protection, and a reaction is carried out to obtain a curing accelerator, and the modified filler is dispersed in ethanol, stirred, and KH560 and deionized water are added to react to obtain a reinforced filler; Step A3: Weigh the following raw materials in parts by weight: 80-90 parts of epoxy resin E-51, 10-20 parts of reinforcing filler and 10-20 parts of 501A epoxy reactive diluent, mix them evenly to obtain component A, weigh the following raw materials in parts by weight: 15-20 parts of curing agent, 5-10 parts of curing accelerator, 100-150 parts of colored sand, 2-5 parts of talcum powder, 0.3-1 parts of dispersant, 0.3-0.5 parts of defoaming agent and 5-10 parts of leveling agent, mix them evenly to obtain component B, mix component A and component B to obtain colored sand self-leveling floor coating.
2. The method for preparing a colored sand self-leveling floor coating according to claim 1, characterized in that: The molar ratio of cardanol, potassium carbonate and allyl chloride in step A1 is 1:1.1:1, and the molar ratio of intermediate 1 and tetramethylcyclotetrasiloxane is 1:
4.
3. The method for preparing a colored sand self-leveling floor coating according to claim 1, characterized in that: The molar ratio of intermediate 2, octamethylcyclotetrasiloxane, tetramethylammonium hydroxide and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane described in step A2 is 1.2:1.2:3:2, and the amount of KH560 used is 5% of the mass of the modified filler.
4. The method for preparing a colored sand self-leveling floor coating according to claim 1, characterized in that: The modified filler is prepared by the following steps: Step B1: dispersing cellulose in N,N-dimethylacetamide, introducing nitrogen protection, stirring and adding anhydrous lithium chloride, stirring, cooling and adding triethylamine and p-toluenesulfonyl chloride to react to obtain pretreated cellulose, dispersing the pretreated cellulose in N,N-dimethylacetamide, stirring and adding ammonia water to react to obtain amino cellulose; Step B2: mixing and reacting aminated cellulose, maleic anhydride, triethylamine and N,N-dimethylformamide to obtain modified cellulose, and uniformly mixing tetramethyltri-3-trifluoropropylcyclotetrasiloxane, octamethylcyclotetrasiloxane, tetramethylammonium hydroxide, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and dimethyl sulfoxide, introducing nitrogen protection, and reacting to obtain a modifier; Step B3: The modifier, allyl glycidyl ether and N,N-dimethylformamide are mixed and reacted to obtain a modified monomer, and the modified monomer, modified cellulose, 1-hexene, azobisisobutyronitrile and N,N-dimethylformamide are mixed evenly, and nitrogen is introduced for protection to react to obtain a modified filler.
5. The method for preparing a colored sand self-leveling floor coating according to claim 4, characterized in that: The mass ratio of cellulose, anhydrous lithium chloride, triethylamine and p-toluenesulfonyl chloride in step B1 is 10 mg: 1 mg: 1 g: 5 g, and the amount ratio of pretreated cellulose, N, N-dimethylacetamide and ammonia water is 1 mL: 10 mL: 20 mL.
6. The method for preparing a colored sand self-leveling floor coating according to claim 4, characterized in that: The molar ratio of the amino group on the aminated cellulose in step B2, maleic anhydride and triethylamine is 1:1:1.2, and the molar ratio of tetramethyltri-3-trifluoropropylcyclotetrasiloxane, octamethylcyclotetrasiloxane, tetramethylammonium hydroxide and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane is 1.5:0.9:3:
2.
7. The method for preparing a colored sand self-leveling floor coating according to claim 4, characterized in that: The molar ratio of the modifier and allyl glycidyl ether in step B3 is 1:4, and the amount ratio of the modified monomer, modified cellulose and 1-hexene is 60mmol:1g:40mmol.
8. A colored sand self-leveling floor coating, characterized in that: Prepared according to any one of claims 1 to 7.
Citation Information
Patent Citations
Epoxy flooring coating containing epoxide group organosilicon hybrid, its preparation method and its application
CN102295875A
Self-leveling sand color terrace material as well as preparation method and construction method thereof
CN104745047A
Aqueous coating material
JP2019038910A